Chemical Diversity and Biological Properties of Secondary Metabolites from Sea Hares of Aplysia Genus - Pereira, Renato B. (Mar Drugs, 2016)
The marine environment is an important source of structurally-diverse and biologically-active secondary metabolites. During the last two decades, thousands of compounds were discovered in marine organisms, several of them having inspired the development of new classes of therapeutic agents. Marine mollusks constitute a successful phyla in the discovery of new marine natural products (MNPs). Over a 50-year period from 1963, 116 genera of mollusks contributed innumerous compounds, Aplysia being the most studied genus by MNP chemists. This genus includes 36 valid species and should be distinguished from all mollusks as it yielded numerous new natural products. Aplysia sea hares are herbivorous mollusks, which have been proven to be a rich source of secondary metabolites, mostly of dietary origin. The majority of secondary metabolites isolated from sea hares of the genus Aplysia are halogenated terpenes; however, these animals are also a source of compounds from other chemical classes, such as macrolides, sterols and alkaloids, often exhibiting cytotoxic, antibacterial, antifungal, antiviral and/or antifeedant activities. This review focuses on the diverse structural classes of secondary metabolites found in Aplysia spp., including several compounds with pronounced biological properties.